The Role for Counter-Cyclical Fiscal Policy in Singapore - Eskesen, Leif (IMF Working Papers; Working Paper ;, 2009)
Singapore's policymakers have often used fiscal policy as a counter-cyclical tool. Empirical results based on a structural autoregression framework suggest that fiscal policy can be used for demand management, although the impact may be somewhat short lived. The short-lived impact could reflect a number of factors, including the absence of credit-constrained economic agents, a high propensity to save among households, monetary focus on price stability, and leakages due to economic openness. Notwithstanding, fiscal policy should still play a key stabilizing role in the current downturn given the downside risks to growth and the vast fiscal space.